About expansion of Crataegus ucrainica A. Pojark (Rosaceae) in Forest-Steppe region of Dnipro left bank (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
It is provided information about expansion of Crataegus ucrainica A. Pojark. according to results of study of herbariums, literature and original researches. Ecological and coenotic features of new locations of species and described the current state and expansion its population are shown. The authors note that main natural habitat is located in Forest-Steppe region of Dnipro left bank. Results of research of locations C. ucrainica, including earlier studied coenopopulation on the Dnipro right bank (on outflow of the Ros river) [Shevchyk et al., 2016], is certified ecological originality of this species. Comparative morphological analysis of herbarium materials helps better identify species and clarify its geographic, ecological and coenotic natural habitat. It is emphasized general necessity of protection of new location of C. ucrainica – rare species on the European and global level.
Keywords: Crataegus ucrainica, rare species, location, protection, Forest-Steppe region of Dnipro left bank.